Stability Analysis of a Weathered-Basalt Soil Slope Using the Double Strength Reduction Method - Xiaoliang Liu; Xin Chen; Mei Su; Shilin Zhang; Dengfeng Lu (Advances in Civil Engineering)
Slope stability analysis of the mountain landforms in southwestern China has always been an important problem in the field of geotechnical engineering. The large landslide occurs in Jichang Town, Shuicheng County, Guizhou Province, China, on July 23, 2019, as the engineering background. Based on the nonlinear relationship between the soil water content, cohesion, and friction angle measured in laboratory tests, the finite element reduction problem of the double-strength parameters is only transformed into a reduction problem of water content. Then, based on the redevelopment platform in the ABAQUS finite element software, a user subroutine to specify predefined field variables (UFIELD) was written to numerically simulate the stability of the Jichang slope before the landslide. The results show that the Jichang slope is mainly composed of basalt-weathered red clay mixed with gravel of various particle sizes. The underlying bedrock is primarily the Permian Emeishan basalt with strong-to-weak weathering and a small amount of argillaceous siltstone. Due to the increase in water content caused by heavy rainfall, the strength of the soil decreased continuously. Once the critical stress state of the slope was exceeded, the plastic sliding block slipped at high speed over a long distance along the rock-soil layer interface, and along the way, it scraped out and carried away the original loose topsoil and gravel blocks, which finally piled up in the form of a debris flow. In addition, the attenuations of the cohesion and friction angle are different. When the water content is less than 25%, the reduction coefficient of the friction angle is greater than the cohesion, which shows that the attenuation of the friction angle is stronger than that of the cohesion. The opposite is true when the water content is greater than 25%. The new method of double-strength finite element reduction presented in this paper is reasonable and feasible and is more in line with the actual situation of weathered-basalt soil slope instability in heavy rainfall areas.